Związki frazeologiczne w edukacji językowej dziecka – zarys problematyki - Kuszak, Kinga (Wydawnictwo Naukowe UAM, 2012)
The article touches on the thread of figurative language embodied in conventional idiomatic combinations in: metaphors, idioms, proverbs. The author analyzed the most important concepts relating to the figurative language using pedagogical, psychological and linguistic literature. She took note of traditional and contemporary sources of idiomatic expressions functioning in the con-temporary language. In the next part she considered the thread of children’s language education and what place dose idiomatic education hold in contemporary propaedeutic education. The article is an introduction into the subject matter of idiomatic expressions functioning in the contemporary language.
Idiomatic expressions in a child’s language education – outline of the problem
Keywords: metaphor; idiom; idiomatic expression; proverb; early school education; language education